Neuroprotective effects of Indigofera tinctoria on noise stress affected Wistar albino rat brain - Sakthivel Srinivasan, Wankupar Wankhar, Sheeladevi Rathinasamy, Ravindran Rajan (Journal of Applied Pharmaceutical Science, 2015)
The objective of the study is to evaluate the DNA damage, behavior and free radical scavenging enzymes level when exposed to noise. Noise stress was performed using broadband white noise generator after pre-treated oral administration of Indigofera tinctoria (300mg/Kg .b.w.). Significance increase in nitric oxide and lipid peroxidation level in stressed rat shows possibility of neurodegeneration and this is justified by genomic DNA damage in brain discrete region. Increase in enzymatic and decrease in non-enzymatic level suggest that oxidative imbalance persist in animal when expose to noise in both brain and adrenal. Anxiety and altered motor coordination was also observed in our studies, this finding could be attributed to the detrimental effects of noise not only at the biochemical level but also the molecular and psychological behavior of the rat. However, oral administration of I. tinctoria significantly prevented noise induced oxidative damages. These results conclude that I. tinctoria may possess neuroprotective effects and the antioxidant property of the plant may have resulted in its therapeutic efficacy.
Keywords: Oxidative stress, DNA fragmentation, Antioxidant, Motor coordination, Anxiety, Behavior.